Determination of hidric performance in the high basin of Grande river in Puno - Sarango, Douglas D. (2012)
Since 2000, different cooperatives, mining enterprises and also some forms of informal clandestine exploitation have been performing heavy minery of gold in the high basin of Rio Grande, of the district of Ananea-Puno. The environmental impact comes from the residues or waste released from the mining activity, being the sediments the ones that cause it. Ways to solve this is impacts is through the construction of a dam to storage and hold these residues. In this sense, in order to design the dam and determine the volumes of sediments to be storaged, it was necessary to determine a series of monthly streamflow at the dam site axis. The high basin of Rio Grande doesn’t count with hydrometric o hydrographic stations, but precipitation occurred is measuring at Ananea´s climatology station. Because of this summary the present investigation uses precipitation - streamflow model to determine streamflows, using as data monthly precipitation and obtaining monthly streamflow. The results shown annual average flow of 3.22 m3/s and the annual average volume of 100.07 MMC at the dam site axis proyected on the higher part of the basin of river Grande.